PENGARUH AFTER SALES SERVICE BERBASIS TEKNIS BUDIDAYA AYAM DAN PROGRAM LOYALTY REWARD TERHADAP KEPUASAN PELANGGAN DALAM MEMBENTUK LOYALITAS PELANGGAN (Studi Pada Pelanggan Pakan Ternak di Kalimantan) - Sofyan Haris; Muhammad Riza Firdaus; Ahmad Rifani (Universitas Lambung Mangkurat, 2017)
The purpose of this research is to know the effect of afters-sales service based on chicken farming technique (X1) and loyalty reward program (X2) as independent variable to customer satisfaction (Y1) in shaping customer loyalty (Y2) animal feed in Kalimantan as dependent variable. The method used in this research is to collect the data with the questionnaire survey technical to the livestock feed customer in Kalimantan Island. Determination of the research sample using non-probability sampling method of purposive sampling type with the criteria has been purchasing feed for more than 3 years, have felt the benefits of the company and have farm broiler, laying hens, ducks. The measurement of variables using the bipolar adjective scale of perfection of the semantic scale with the two extreme categories